PENGARUH TARI RODAD HADRAH TERHADAP RELIGIOSITAS REMAJA - Mufidatul Munawaroh; Suroso Suroso; Muhammad Farid (JIP (Jurnal Intervensi Psikologi), 2019)
This study aims to know the effect of Hadrah Rodad Dance on adolescent religiosity. The subject of this study is male adolescents, who are 12 to 15 years old and being students of Islamic Junior High School (MTs) in Lamongan regency. There are 60 adolescents who are chosen, and they are grouped into two groups randomly. The first group consists of 30 adolescents as an experimental group. The second group consists of 30 adolescents as a control group. Type of this study is experimental research using pretest-posttest control group design. The research data is taken by using a religiosity scale. The data analysis technique used is analysis of covariance (ANACOVA) which is obtained by F = 67,744 and Sig/p = 0,00. It means that there is a significant difference between the group of adolescent religiosity which gets the treatment of hadrah rodad dance (experimental group) and the group of adolescents who do not get the treatment of hadrah rodad dance (control group). After the groups have been given the treatment of hadrah rodad dance, there are different results of the groups. The religiosity average of the experimental group is 37,37 which is higher than the religiosity average of the control group, that is 5,76. The results of the study prove that the dance of hadrah rodad is an effective way to improve adolescent religiosity.